Photo Nitroxide-Mediated Living Radical Polymerization of Hindered Amine-Supported Methacrylate - Yoshida, Eri (Journal of Research Updates in Polymer Science, 2018)
With the aim of obtaining giant polymer vesicles supporting a hindered amine that is converted into a redox catalyst on the vesicle shells, the living nature of the photo nitroxide-mediated living radical polymerization (photo NMP) of a monomer containing a hindered amine and the formation of the vesicles consisting of an amphiphilic diblock copolymer by the polymerization-induced self-assembly were investigated. The photo NMP of 2,2,6,6-tetramethyl-4-piperidyl methacrylate (TPMA) was performed in methanol using 4-methoxy-2,2,6,6-tetramethylpiperidine-1-oxyl (MTEMPO) as the mediator, 2,2’-azobis[2-(2-imidazolin-2-yl)propane] (V-61) as the initiator, and (4-tert-butylphenyl)diphenylsulfonium triflate as the accelerator by UV irradiation at room temperature. The first-order time-conversion plots had an induction period in which the MTEMPO molecules were captured by the initiator radicals and the monomer radicals generated by the initiation. It was confirmed that the polymerization proceeded by a living mechanism based on linear correlations of the molecular weight of the poly(TPMA) (PTPMA) versus the monomer conversion and the reciprocal of the initial concentration of V-61. Based on the livingness of the polymerization, the photo NMP-induced self-assembly for the block copolymerization of methyl methacrylate (MMA) using the PTPMA end-capped with MTEMPO was carried out in methanol to produce microsized giant spherical vesicles consisting of the amphiphilic PTPMA-block-poly(MMA) diblock copolymer. A differential scanning calorimetry study demonstrated that the vesicles had a single bilayer structure.